CCR5 conformations are dynamic and modulated by localization, trafficking and G protein association. - Ayanna J Flegler; Gianguido C Cianci; Thomas J Hope (PLoS ONE, 2014)
CCR5 acts as the principal coreceptor during HIV-1 transmission and early stages of infection. Efficient HIV-1 entry requires a series of processes, many dependent on the conformational state of both viral envelope protein and cellular receptor. Monoclonal antibodies (MAbs) are able to identify different CCR5 conformations, allowing for their use as probes to distinguish CCR5 populations. Not all CCR5 MAbs are able to reduce HIV-1 infection, suggesting the use of select CCR5 populations for entry. In the U87.CD4.CCR5-GFP cell line, we used such HIV-1-restricting MAbs to probe the relation between localization, trafficking and G protein association for individual CCR5 conformations. We find that CCR5 conformations not only exhibit different localization and abundance patterns throughout the cell, but that they also display distinct sensitivities to endocytosis inhibition. Using chemokine analogs that vary in their HIV-1 inhibitory mechanisms, we also illustrate that responses to ligand engagement are conformation-specific. Additionally, we provide supporting evidence for the select sensitivity of conformations to G protein association. Characterizing the link between the function and dynamics of CCR5 populations has implications for understanding their selective targeting by HIV-1 and for the development of inhibitors that will block CCR5 utilization by the virus.